Digital teacher performance management in a border area school : implementation of the ruang GTK platform and its impact on work effectiveness - Yulia Septemi; Sudarwan Danim; Azizatul Khairi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
Digital platforms are increasingly used for teacher performance management, yet evidence from under-resourced contexts, particularly border-area schools, remains limited. This study examines the implementation of teacher performance management using the Ruang Guru dan Tenaga Kependidikan (Ruang GTK) platform and its contribution to teacher work effectiveness in a public junior high school located in an Indonesian border area. A qualitative descriptive approach was employed. Data were collected through semi-structured interviews, non-participant observations, and document analysis involving the principal, six teachers, and one school operator. Data were analyzed using the interactive model of Miles and Huberman. The findings show that Ruang GTK was implemented across five performance management stages: planning, implementation, monitoring and feedback, evaluation and reflection, and professional development. The platform contributed to clearer work direction, improved task organization, increased discipline, and supported reflective practices. However, constraints included unstable internet access, varying teacher digital literacy, and inconsistent system use. One teacher stated, “I often struggle to upload evidence because the internet connection is unstable.” Ruang GTK has potential as a digital performance management tool in border-area schools, but its effectiveness depends on infrastructure readiness, digital competence, and leadership support. Schools should provide targeted training and ensure reliable internet access. Future research should examine implementation across multiple schools.